Certification of medical librarians, 1949--1977 statistical analysis. - Schmidt, D (1979)
The Medical Library Association's Code for Training and Certification of Medical Librarians was in effect from 1949 to August 1977, a period during which 3,216 individuals were certified. Statistics on each type of certificate granted each year are provided. Because 54.5% of those granted certification were awarded it in the last three-year, two-month period of the code's existence, these applications are reviewed in greater detail. Statistics on each type of certificate granted each year are provided. Because 54.5% of those granted certification were awarded it in the last three-year, two-month period of the code's existence, these applications are reviewed in greater detail. Statistics on MLA membership, sex, residence, library school, and method of meeting requirements are detailed. Questions relating to certification under the code now in existence are raised.